Strategi Recep Tayyip Erdogan dalam Memanfaatkan Isu Pengungsi pada Pemilu Turki 2023: Analisis Perspektif Soft Power - Nurilah Fitrah Syamsuddin; M. Syaroni Rofii (Universitas Medan Area, 2026)
The 2023 Turkish election marked a significant moment in Turkey’s domestic political dynamics and reflected changes in its position within the international order. One of the central issues dominating the political contestation was the refugee crisis, particularly concerning Syrian refugees, which has become a prolonged challenge for the Turkish government. This study aims to analyze Recep Tayyip Erdogan’s strategy in utilizing the refugee issue as an electoral political instrument through a soft power perspective. This research employs a qualitative approach using a case study method, based on secondary data collected from academic journals, policy documents, and relevant news sources. The findings reveal that Erdogan pragmatically employed anti-refugee rhetoric to strengthen domestic political support, despite contradicting Turkey’s previous image as a humanitarian protector. This strategy reflects a transformation of Turkey’s soft power into a form of negative soft power, where humanitarian issues are instrumentalized for domestic political interests but potentially weaken Turkey’s attractiveness and legitimacy at the international level. These findings suggest that Erdogan’s pragmatic politics seek to balance electoral interests, national stability, and Turkey’s global image amid the refugee crisis.